Pengembangan Model Pembelajaran Smartberbasis Steam Untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa Pada Mata Pelajaran Prakarya - Eko Sulistyawan (Jurnal Didaktika Pendidikan Dasar, 2020)
Creative thinking skills are one of the competencies that must be had in welcoming the era of the industrial revolution 4.0. So the learning process should be oriented to competence. The learning model used by STEAM-based learning model that utilizes Android games as a stimulus. The approach used in this study is a qualitative descriptive approach to the aspects of validity and practicality as well as quantitative pre-experimental (one group pretest posttest design). The results of the validation of the learning model by expert validators show a mean score of 81.50 which means that the SMART learning model obtains valid criteria. The results of observations of the implementation of STEAM aspects in the syntax of the SMART learning model showed quite good criteria in the aspects of science, technology and mathematics, as well as criteria both in engineering and art aspects. The results of the effectiveness of the learning model trials in grade VII students of Singosari One Roof Junior High School in the academic year 2017/2018 using one group pretest posttest design research design showed an increase in students' creative thinking skills from 53.64 to 86.00 and the product test results reached 84, 88. This shows that the STEAM-based SMART learning model developed is suitable for use in the learning process.